A glossary of corpus linguistics - Baker, Paul, 1972- (Edinburgh University Press, 2006)
This alphabetic guide provides definitions and discussion of key terms used in corpus linguistics. Corpus data is being used in a growing number of English and Linguistics departments which have no record of past research with corpus data. This is the first comprehensive glossary of the many specialist terms in corpus linguistics and will be useful for corpus linguists and non corpus linguists alike. Clearly written, by a team of experienced academics in the field, the glossary provides full coverage of both traditional and contemporary terminology. Entries are focused around the following broad groupings: Important corpora Key technical terms in the field Key linguistic terms relevant to corpus-based research Key statistical measures used in corpus linguistics Key computer programme/retrieval systems used in the construction and exploitation of corpora Standards applied within the field of corpus linguistics.